DYNAMIC EVALUATION AND TEST OF ORALS: DIGITAL EFFICACY ON UNIVERSITY UNDERGRADUATES’ PERFORMANCE IN SOUTHWEST NIGERIA - Bankole Olagunju Faloye; Kolawole Thomas Ajisola (International Journal of Social Science, 2023)
This paper presents a study exploring the efficacy of customised software, dynamic evaluation and Test of Orals (TEO) on the performance of university undergraduates in Southwest Nigeria. A multistage sampling procedure was used in selecting 200 students from two public universities in Southwest Nigeria. A quasi-experimental design and descriptive survey-type research design were used to investigate the impact of customised software ( Kollit ) on 200 students randomly selected for the study. Two hypotheses were raised. The instrument for data collection was the Students' Oral English Proficiency Test (SOEPT). The Cronbach Alfa method was used to establish the reliability coefficient for SOEPT, which was found to be 0.68. A One-Way Analysis of Variance was utilised to test the hypotheses at a 0.05 significance level. The study results indicated a significant increase in academic performance on the part of the students after implementing the customised software. The findings suggested that the customised software could improve the performance and evaluation of students in the Test of Orals. The study concludes by discussing the potential limitations of the study while offering recommendations for future research